2013
DOI: 10.1175/jcli-d-12-00196.1
|View full text |Cite
|
Sign up to set email alerts
|

Transient Climate Response in a Two-Layer Energy-Balance Model. Part II: Representation of the Efficacy of Deep-Ocean Heat Uptake and Validation for CMIP5 AOGCMs

Abstract: In this second part of a series of two articles analyzing the global thermal properties of atmosphere-ocean coupled general circulation models (AOGCMs) within the framework of a two-layer energy-balance model (EBM), the role of the efficacy of deep-ocean heat uptake is investigated. Taking into account such an efficacy factor is shown to amount to representing the effect of deep-ocean heat uptake on the local strength of the radiative feedback in the transient regime. It involves an additional term in the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
276
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(285 citation statements)
references
References 20 publications
8
276
1
Order By: Relevance
“…A number of studies have attributed this strengthening of the feedbacks to changes in the pattern of surface warming (Williams et al, 2008), mainly in the eastern tropical Pacific where an intensification of warming can occur after a few decades, but also in other regions such as the Southern Ocean . The impact of variations in ocean heat uptake has also been suggested to be a contributing factor (Geoffroy et al, 2013;Held et al, 2010;Winton et al, 2010).…”
Section: Gregory Plotsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have attributed this strengthening of the feedbacks to changes in the pattern of surface warming (Williams et al, 2008), mainly in the eastern tropical Pacific where an intensification of warming can occur after a few decades, but also in other regions such as the Southern Ocean . The impact of variations in ocean heat uptake has also been suggested to be a contributing factor (Geoffroy et al, 2013;Held et al, 2010;Winton et al, 2010).…”
Section: Gregory Plotsmentioning
confidence: 99%
“…A limitation of this approach is that it assumes that the response of climate to a forcing is linear after the first 20 years, which has been shown to be unlikely in longer simulations of several decades or centuries Armour et al, 2013;. However, a comparison of the difference in temperature response to upper-and deep-ocean heat uptake and its contribution to the relationship between net radiative flux change (N) and global temperature change ( T ) in Geoffroy et al (2013) indicated that the method of of fitting two separate linear models to the early and subsequent (N, T ) data gives a good approximation of T g eq , F and α as they have been calculated here. A study by Li et al (2013) also found that, using the Gregory plot methodology, T g eq was estimated to within 10 % of its ac- tual value, obtained by running the simulation very close to equilibrium (∼ 6000 years).…”
Section: Gregory Plotsmentioning
confidence: 99%
“…That is, the surface temperature change and the ocean heat uptake hold a linear relation under constant radiative forcing in the two-layer model. Geoffroy et al (2013a) applied this model to analyze the CMIP5 AOGCM simulations and showed that the two-layer models tuned to emulate the global mean surface temperature response of AOGCMs in the abrupt4xCO2 experiment can also emulate the result of the slowly increasing CO 2 (1pctCO2) experiment reasonably well. This supports the assumption that the two-layer model is effective in capturing the minimal physics of the global mean surface temperature transient response.…”
Section: Time Scale Of the Responsementioning
confidence: 99%
“…4c, black), equal to the range of ε displayed in CMIP5 models evaluated by Geoffroy et al (2013). 3.…”
Section: Monte Carlo Input Parameter Distributionsmentioning
confidence: 99%